(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
The purpose of this study was to explain and analyze the absorption of the Petroleum Engineering Study Program, Faculty of Engineering, Universitas Proklamasi 45 Yogyakarta in the world of the oil and gas industry. The method used is a qualitative research method, with the type of research that is descriptive. This research was conducted by conducting observations, interviews, and documentation, with the research location being the Petroleum Engineering Study Program, Faculty of Engineering, Universitas Proklamasi 45 Yogyakarta. The research instrument in the form of a list of questions asked directly to the relevant resource persons. The results showed that the absorption rate of Alumni of the Petroleum Engineering Study Program, Faculty of Engineering, Universitas Proklamasi 45 Yogyakarta in the world of work of oil and gas companies in 2019 to 2021 were 28%, 13.33%, and 8%, respectively. Thus, from year to year the absorption of alumni of the Petroleum Engineering Study Program, Faculty of Engineering, Universitas Proklamasi 45 Yogyakarta has decreased. This is due to several factors including: lack of mastery of English language skills, lack of availability of facilities, lack of alumni associations and not having certification in the oil and gas sector. In order to increase the absorption of Alumni of the Petroleum Engineering Study Program, Faculty of Engineering, Universitas Proklamasi 45 Yogyakarta in the world of work for oil and gas companies, the efforts currently being developed by the Petroleum Engineering Study Program, Faculty of Engineering, Universitas Proklamasi 45 Yogyakarta, need support from various parties, both from internal parties (the entire academic community) and external parties (alumni and other stakeholders).